Performance Chickens Kedu, Arab and Its Cross Breeds (Poncin) Of Distribution Content Protein Of Growth Fase (Age 0 -12 Week) - I. Irmawaty; Tuti Widjastuti; Asep Anang; Muhammad Nur Hidayat (Chalaza Journal of Animal Husbandry, 2020)
This experiment shows performance chickens of Kedu, Arab, and Poncin with Giffen different protein content.  This experiment uses chickens of Kedu, Arab, and Poncin (a crossbreed of male Arab and female Kedu) that each breed consists of 40 Day Old Chicken. Each species was randomly placed in 8 units of experiment cage, and every experiment cage consists of 5 Day Old Chicken.  Treatment dietary is used 15% (R1) dan 18% (R2).  The experiment's design is used a completely random design 2x3 factorial, that i two treatments of dietary and three breeds of chickens. Every treatment is replayed four times, and the show used 24 units of experiment cage.  The parameter is limited watch on dietary Consumption, body weight gain, and feed conversion. The result showed that Poncin chickens gave better growth performance when compared to Arab and Kedu chickens. Simultaneously, the ration protein content of 18 % resulted in better growth performance compared to 15% ration protein.